Selling the product: Strategies to increase recruitment and retention of Spanish-speaking Latinos in biomedical research. Issue 3 (22nd October 2018) - Rhodes, Scott D.; Alonzo, Jorge; Mann-Jackson, Lilli; Tanner, Amanda E.; Vissman, Aaron T.; Martinez, Omar; Rodriguez-Celedon, Rodrigo; Garcia, Jesus M.; Arellano Hall, Jorge E.; Song, Eunyoung Y.; Eng, Eugenia; Reboussin, Beth A.
Abstract : Introduction: The Latino population in the United States is rapidly growing and faces profound health disparities; however, engagement of Latinos in biomedical research remains low. Our community-based participatory research partnership has recruited 2083 Spanish-speaking Latinos into 21 studies over 15 years. We sought to identify and describe the strategies we have used to successfully recruit and retain Spanish-speaking Latinos in research. Methods: We abstracted and analyzed data from archived study notes, progress reports, team meeting minutes, and in-depth interviews conducted annually from community-based participatory research partnership members. We used a nominal group process to refine and prioritize strategies. Results: Overall, 13 recruitment strategies and 12 retention strategies emerged. These strategies relied on the creativity and perseverance of the study team and partners. Conclusions: It is essential that we develop and disseminate effective recruitment and retention strategies that engage Latinos in biomedical research to reduce health disparities and promote health equity.